Effect of shelling ratios on the sorption and flexural properties of cement bonded particleboard produced from mixed Nigerian hardwood species (2014)
Panel layer characteristics, otherwise referred to as shelling ratio, relate to the proportional ratio between the thickness of the fine surface layer and flake core layer materials in a 3-layered particleboard. The experiment was carried out in order to determine the most favourable core-surface thickness ratio at which board properties are maximized. To achieve this, experimental cement-bonded particleboards were made using three sawdust surface/flake core layer thickness ratios d 1 : 2, 1 : 1 and 2 : 1. Each of the ratio was considered at two board density IeveIs of 1100 and 1200 kg/m3 and two cement/wood mixing ratio of 2.25 : 1.0 and 2.75: 1.0. The experimental arrangement is a three-factor factorial experiment which manifested in 12 treatment combinations. The experimental boards produced were subjected to modulus of rupture (MOR), modulus oSf elasticity (MOE), water absorption (WA), thickness swelling (TS) and linear expansion (LE) tests. Data collected were subjected to statistical analysis using ANOVA and multiple linear regressions. The mean Moduli of Rupture and Elasticity (MOR and MOE) obtained ranged from 4.23 to 11.92 N/mm2 and 1950 to 4140 N/mm2 respectively. Water absorption (WA) and thickness swelling (TS) ranged from 24.75 to 10.58% (WA) a d 0.41 to 4.01% (TS). It noted that the mean values of MOR and MOE obtained at the sawdust surface layer/flake core layer thickness ratio of 1 : 2 were significantly superior at 5% level of probability to those obtained at the thickness ratio levels of 1 : 1 and 21.1. On the other hand however, the mean values of WA and TS obtained at the sawdust surface layer/flake core layer thickness ratio of 2 : 1 were significantly superior at 5% level of probability to those obtained at thickness ratio levels of 1 : 2 and 1 : 1. of sawdust to flake contents of board. The highest strength and stiffness values obtained at the thickness ratio level of 1 : 2 of sawdust surface layer flake core layer notwithstanding, the thickness ratio level of 2 :1, which implies cement-bonded particleboard production at increased sawdust content and decreased flake content, was selected applied as a the optimum. This being so, in view of the fact that the overriding objective of the study was to 6 mm thick cement-bonded particleboards which could be resistant to moisture and adequate for house ceiling.